2017
DOI: 10.3126/jcmc.v6i1.16651
|View full text |Cite
|
Sign up to set email alerts
|

A prospective assessment of polypharmacy induced drug interactions with corticosteroids

Abstract: Drug interaction represents a major problem in day-to-day practice. The incidence of adverse reactions increases almost exponentially as the number of drugs co prescribed rises, and this is in part due to interaction. This study was aimed to study the incidence of polypharmacy induced drug interactions with corticosteroids and their severity. A prospective observational study was carried out in 211 In-patients from various departments of the hospital during 6 months and subjected to statistical analysis. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
2
1
0
Order By: Relevance
“…In 90 prescriptions total 24 interactions were found out of which 4 (16.67%) were minor, 15 were (62.50%) moderate and 5 (20.83%) were major. Mostly moderate interactions were found in the study which was consistent with the study of Kumar S, et al 11 . who found that 80% of the interactions were moderate, 13% were major and 55.8% were contraindicated interactions subsequent the use of corticosteroids in his study.…”
Section: Discussion:-supporting
confidence: 91%
“…In 90 prescriptions total 24 interactions were found out of which 4 (16.67%) were minor, 15 were (62.50%) moderate and 5 (20.83%) were major. Mostly moderate interactions were found in the study which was consistent with the study of Kumar S, et al 11 . who found that 80% of the interactions were moderate, 13% were major and 55.8% were contraindicated interactions subsequent the use of corticosteroids in his study.…”
Section: Discussion:-supporting
confidence: 91%
“…In this study out of 200 prescriptions total 27 interactions were found out of which 7 (25.93%) were minor, 15 were (62.56%) moderate and 5 (18.52%) were major. Mostly moderate interactions were found in the study which was consistent with the study of Kumar S, et al [24]. who found that 80% of the interactions were moderate, 13% were major and 55.8% were contraindicated interactions subsequent the use of corticosteroids in his study.…”
Section: Discussionsupporting
confidence: 90%
“…The study has shown that 1/3rd reduction in sodium excretion can affect the treatment of patient adversely for the patient treated with spironolactone for ascites or edema [11]. Another study shows that Dexamethasone, Ciprofloxacin, Tramadol, Moxifloxacin, Diclofenac, Pantoprazole and Theophylline [12]. The level of evidence provided by the online database for the given major drug interaction were majorly of poor level of evidence i.e., 71 drug interaction with level 5 evidence followed by 15 drug interactions of 3b, 10 drug interaction of 1b, 6 drug interaction of 4 and 5 drug interaction of 2b.…”
Section: Discussionmentioning
confidence: 99%